1996
DOI: 10.1002/macp.1996.021971029
|View full text |Cite
|
Sign up to set email alerts
|

Polynorbornene: synthesis, properties and simulations

Abstract: The vinylic polymerization of norbornenes upon catalysis with Pd2' complexes with norbornylnitrile as ligands is reported. The polynorbornenes (a,,, = lo6) display a set of unique properties including a dense packing in the amorphous state, high glass transition temperatures, large refractive index, low birefringence and significant brittleness. To test the concept that these properties can be traced back to the conformational constraints of the polymer chains, we performed ab initio calculations, semi-empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
140
3
2

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(162 citation statements)
references
References 26 publications
17
140
3
2
Order By: Relevance
“…Both spectra display two broad halos at 2u of 10 and 18.5Њ that can be attributed to a short range order. This is in agreement with the results reported by Haselwender et al [4]. No traces of Bragg reflections, characteristic of crystalline regions, are revealed.…”
Section: X-ray Diffraction and Polymer Packingsupporting
confidence: 94%
See 4 more Smart Citations
“…Both spectra display two broad halos at 2u of 10 and 18.5Њ that can be attributed to a short range order. This is in agreement with the results reported by Haselwender et al [4]. No traces of Bragg reflections, characteristic of crystalline regions, are revealed.…”
Section: X-ray Diffraction and Polymer Packingsupporting
confidence: 94%
“…The polynorbornene is therefore non-crystalline. Haselwander et al [4] state that the two amorphous halos shown by polynorbornene are of intrachain nature, according to the specific structural information provided by the amorphous cell calculation. Nevertheless we tend to believe, in accordance with the investigations of polystyrene [14] and other polymers [15], that at least one amorphous halo, the one at relatively low angle, can be regarded as a reflection of the interchain or intersegment distance of the polymer.…”
Section: X-ray Diffraction and Polymer Packingmentioning
confidence: 99%
See 3 more Smart Citations